Digital Literacy at The University (Journal of the College of Education for Women, 2019)
The revolution of technology in the 21st century has changed radically theclimate of opinion concerning second language education. In order to excel intoday’s world, teachers and learners need to adopt new roles and be equipped withnew skills and competencies that go beyond the basic ones of listening, speaking,reading, and writing; skills that cannot be gained if teachers teach mere academicsubjects, and students are evaluated on how well they have learnt the minute subskills in those content areas.This session will touch upon several skills which may be considered thenew basics of the 21st century. Among these skills are: autonomy, active learning,critical thinking, cooperative learning, and digital learning (AACCD). Digitalliteracy with its opportunities and challenges will be the core of this session due toits novelty which makes it worth studying. It will also explore university teachers’attitudes towards using digital learning. The session will end up with somesuggestions for consideration if teachers and educators are truly looking forward toexcellence in the ELT profession.